Incidence and prevalence of aphid-borne viruses infecting strawberry in Argentina - Luciani, Cecilia Elizabeth; Celli, Marcos Giovani; Torrico Ramallo, Ada Karina; Asinari, Florencia; Pozzi, Elizabeth Alicia; Peña Malavera, Andrea Natalia; Kirschbaum, Daniel Santiago; Perotto, Maria Cecilia; Conci, Vilma Cecilia (Wiley, 2018)
The incidence and prevalence of strawberry viruses were determined in surveys of randomly selected strawberry plants grown in different regions of Argentina. In 2009 and 2010, 1034 plants from 28 fields and 1060 plants from 33 fields, respectively, were collected from Lules and Coronda. The samples were analysed by double‐antibody sandwich enzyme‐linked immunosorbent assay to detect Strawberry mild yellow edge virus (SMYEV). In 2014, 606 plants from 43 fields in Lules, Coronda and Mar del Plata were analysed by reverse transcription polymerase chain reaction with primers specific for SMYEV, Strawberry crinkle virus (SCV), Strawberry mottle virus (SMoV) and Strawberry polerovirus 1 (SPV1). The SMYEV incidence was 4–35%, while prevalence was 60–100%, depending on the year and region sampled. Meanwhile, SMoV and SPV1 incidences were 8–17%, and prevalences were 46–62%, depending on the virus and region sampled. SCV was observed relatively low (incidence was 0.5–8% and prevalence was 8–50%), although it was more abundant in Mar del Plata than in the other analysed regions. Spearman's correlation analysis indicated that SCV and SMYEV were correlated with disease symptoms (P < 0.005). A principal component analysis revealed a close relationship between SMYEV and SCV in Mar del Plata, in which the lowest temperatures were recorded. Interactions among viruses, regions and climatic conditions will need to be studied in greater detail. Accurately determining the incidence and prevalence of viruses in different regions will improve estimations of possible damages or yield decreases caused by viral infections during strawberry production.